Optimization of Traffic Light Settings on The Toll Overpass Segment of Sidodadi In Sidoarjo Regency - Riezki Latif, Helmi; Marleno, Risma; Muhammadun, Haris (Green Publisher Indonesia, 2025)
The optimization of traffic light settings plays a crucial role in managing vehicle flow, reducing congestion, and improving road performance, particularly in critical segments such as the toll overpass of Sidodadi in Sidoarjo Regency. This study focuses on addressing two key research questions: the impact of heavy vehicle traffic on intersection performance and the effectiveness of proposed strategies for long-term traffic management. Using the Indonesian Highway Capacity Manual (MKJI) 1997, traffic data during peak hours were analyzed to identify delays, degree of saturation, and service levels under existing traffic conditions. The findings revealed that the high volume of heavy vehicles significantly exacerbates delays and reduces intersection efficiency. To address this, two main strategies were proposed: restricting the operational hours of heavy vehicles and implementing dedicated heavy vehicle lanes. Additionally, long-term measures, including intersection redesign and the application of Adaptive Traffic Control Systems (ATCS), were evaluated. The results highlight the need for immediate interventions and continuous evaluation to ensure sustainable traffic flow and support regional mobility and economic growth.